Assessment of the Vulnerability to Pesticide Exposures Across Bee Species. (8th August 2021) - Schmolke, Amelie; Galic, Nika; Feken, Max; Thompson, Helen; Sgolastra, Fabio; Pitts‐Singer, Theresa; Elston, Charlotte; Pamminger, Tobias; Hinarejos, Silvia
Abstract: In many countries, the western honey bee is used as surrogate in pesticide risk assessments for bees. However, uncertainty remains in the estimation of pesticide risk to non‐ Apis bees because their potential routes of exposure to pesticides, life histories, and ecologies differ from those of honey bees. We applied the vulnerability concept in pesticide risk assessment to 10 bee species including the honey bee, 2 bumble bee species, and 7 solitary bee species with different nesting strategies. Trait‐based vulnerability considers the evaluation of a species at the level of both the organism (exposure and effect) and the population (recovery), which goes beyond the sensitivity of individuals to a toxicant assessed in standard laboratory toxicity studies by including effects on populations in the field. Based on expert judgment, each trait was classified by its relationship to the vulnerability to pesticide exposure, effects (intrinsic sensitivity), and population recovery. The results suggested that the non‐ Apis bees included in our approach are potentially more vulnerable to pesticides than the honey bee due to traits governing exposure and population recovery potential. Our analysis highlights many uncertainties related to the interaction between bee ecology and the potential exposures and population‐level effects of pesticides, emphasizing the need for more research to identify suitable surrogate species for higher tier bee risk assessments. Environ Toxicol Chem 2021;40:2640–2651. © 2021 SETAC